Evaluation of career planning tools for use with individuals with autism spectrum disorder: A systematic review - Murray, N.; Hatfield, M.; Falkmer, M.; Falkmer, Torbjorn (2016)
This systematic review aimed to identify tools published in peer reviewed journals that could be utilised in career planning for individuals with autism spectrum disorder (ASD), and to describe their clinical utility and psychometric properties. Due to limited results for ASD-specific tools, the search was broadened to career planning tools for individuals with a cognitive or developmental disability, which could be used by individuals with ASD. Six databases were electronically searched. Main search terms used were 'disability', 'young adult', 'assessment' and 'employment'. Boolean operators expanded the search strategy. Two independent reviewers undertook data extraction and quality assessment. Electronic searches located 2348 literature items; 14 articles met inclusion criteria covering 10 career planning tools. Identified tools were of a predictive nature; however, none of the studies assessed all the psychometric properties necessary for evaluating a sound predictive tool. Only one addressed all three components of clinical utility. None of the identified tools had strong reliability or validity and their clinical utility remains unexplored.